Another "Fourpenny wilderness" in which may be found more nails for the coffin of nonsens called athenism, more hints o freethinkers and a reply to G.J. Holyoake's "Examniation of G. Southwell's Impossibility of atheism demonstrated" (London)
PAMPHLET VOLUME.